2021
DOI: 10.1080/09500693.2021.1959958
|View full text |Cite
|
Sign up to set email alerts
|

Exploring students’ visualisation competence with photomicrographs of villi

Abstract: Photomicrographs are representations of small-scale entities. It has been long argued that students can be weak in perceiving microscopic entities compared to macroscopic entities. However, only a small body of research has investigated how students utilise photomicrographs to make sense of biological phenomena. This study uses a theoretical construct, "visualization competence", to explore students' skills and practices in utilising photomicrographs. Fifty UK students' visualization competence with photomicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Only 9.4% of students scored full marks in the results section (B), emphasizing drawing and labelling. The findings were supported by [1], which explored students' visualization competence and found that they are weak in perceiving microscopic entities through drawing and labelling. They reported that 60.0% of the students could not label their biological drawings, and a higher proportion of students tend to give fewer labels [1].…”
Section: Literature Reviewmentioning
confidence: 69%
“…Only 9.4% of students scored full marks in the results section (B), emphasizing drawing and labelling. The findings were supported by [1], which explored students' visualization competence and found that they are weak in perceiving microscopic entities through drawing and labelling. They reported that 60.0% of the students could not label their biological drawings, and a higher proportion of students tend to give fewer labels [1].…”
Section: Literature Reviewmentioning
confidence: 69%
“…Considering the strong underlying relationship between visual balance and harmony, it might be, however, not entirely a question of preference. Potential ways to operationalize the holistic design considerations are from Dondis (1973) as cited in Muehlenhaus (2013), whose work suggested that persuasive maps could sometimes ignore and defy established cartographic conventions for effective visual communications in society (Cheung & Winterbottom, 2021a, 2021b). How schematic maps are artistically comprised and can be persuasive is worth future investigation for better capturing harmony as part of the design and evaluation process.…”
Section: Discussionmentioning
confidence: 99%
“…In recent research, the automated generation of schematic maps has been treated as an optimization 1 problem according to the researchers' understanding of the usability criteria (Bekos et al, 2022; Nöllenburg & Wolff, 2011; Ti et al, 2015). They have worked with constraints that govern different properties.…”
Section: Literature Reviewmentioning
confidence: 99%